2018
DOI: 10.1038/s41419-018-1074-z
|View full text |Cite
|
Sign up to set email alerts
|

Efferocytosis of apoptotic alveolar epithelial cells is sufficient to initiate lung fibrosis

Abstract: Type II alveolar epithelial cell (AEC) apoptosis is a prominent feature of fibrotic lung diseases and animal models of pulmonary fibrosis. While there is growing recognition of the importance of AEC injury and apoptosis as a causal factor in fibrosis, the underlying mechanisms that link these processes remain unknown. We have previously shown that targeting the type II alveolar epithelium for injury by repetitively administering diphtheria toxin to transgenic mice expressing the diphtheria toxin receptor off o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Mounting evidence has shown that the apoptosis of type II alveolar epithelial cells leads to persistent and excessive migration and activation of fibroblast in the lung interstitium, leading to subsequent generation and accumulates myofibroblasts, which is closely associated with the progression of pulmonary fibrosis. It is likely that loss of the anti-fibrotic characteristics of intact epithelial cells and the increasing secretion of profibrotic factors from injured epithelial cells causes fibrosis [ 42 ]. In the present study, we also found that MenSCs can alleviate BLM-induced apoptosis of MLE-12 cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that the apoptosis of type II alveolar epithelial cells leads to persistent and excessive migration and activation of fibroblast in the lung interstitium, leading to subsequent generation and accumulates myofibroblasts, which is closely associated with the progression of pulmonary fibrosis. It is likely that loss of the anti-fibrotic characteristics of intact epithelial cells and the increasing secretion of profibrotic factors from injured epithelial cells causes fibrosis [ 42 ]. In the present study, we also found that MenSCs can alleviate BLM-induced apoptosis of MLE-12 cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Instillation of Ox-PC directly into the mouse lung induced foam cell formation and accumulation and development of PF. The increased accumulation of lipids in macrophages occurs through efferocytosis whereby macrophages engulf apoptotic alveolar type II epithelial cells after injury via CD36 on the macrophages [319][320][321]. Targeted deletion of the lipid efflux transporter, ATP-binding cassette sub-family G member 1 (Abcg1) increased foam cell formation and exacerbated lung fibrosis in mice from bleomycin challenge [320].…”
Section: Lipid Peroxidation and Oxidized Phospholipids In Pulmonary Fmentioning
confidence: 99%
“…The increased accumulation of lipids in macrophages occurs through efferocytosis whereby macrophages engulf apoptotic alveolar type II epithelial cells after injury via CD36 on the macrophages [319][320][321]. Targeted deletion of the lipid efflux transporter, ATP-binding cassette sub-family G member 1 (Abcg1) increased foam cell formation and exacerbated lung fibrosis in mice from bleomycin challenge [320]. Thus, a pneumocytes-macrophage-CD36-oxidized lipid signaling axis has been proposed to play a key role in the development of lung fibrosis in the bleomycin model [319,322].…”
Section: Lipid Peroxidation and Oxidized Phospholipids In Pulmonary Fmentioning
confidence: 99%
“…Regarding the pathology of fibrosis, phagocytosis of apoptotic cells was reported to induce the production of pro-fibrotic cytokines, such as TGF-β, by macrophages [40][41][42]. TGF-β has been regarded as a key molecule for fibrosis regulation, and further induces the expression of connective tissue growth factor (CTGF) through a functional Smad3-binding site in the CTGF promoter [43].…”
Section: Interaction Between Structured and Non-structured Cells In Tmentioning
confidence: 99%